Understanding the Motivation of Western Java Smallholder Broiler Farmers to Uptake Measures Against Highly Pathogenic Avian Influenza (HPAI) - Pramuwidyatama, Muchammad Gumilang; Hogeveen, Henk; Saatkamp, Helmut W. (Frontiers in Veterinary Science, 2020)
Understanding broiler farmers’ intention towards Highly Pathogenic Avian Influenza (HPAI) control is important to design successful HPAI control programs. We used Theory of Planned Behavior (TPB) to identify factors (i.e., attitude, subjective norm, and perceived behavioral control) associated with the intentions of Western-Java small-scale broiler farmers towards implementing cleaning and disinfection (C&D), vaccination, reporting, and stamping-out without or with 50% compensation. For this, 203 Western-Java farmers were interviewed. The majority of the farmers had a positive intention to implement C&D (89%), reporting (88%), and vaccination (80%). A lower number had a positive intention to join stamping-out both with 50% compensation (67%) and without any compensation (53%). Farmers had a more positive attitude and subjective norm, but lower perceived behavioral control towards one or more of the intentions to implement measures. Attitude was positively associated with intentions to implement C&D and vaccination. Subjective norm of veterinarians of integrated companies was positively associated with intentions to implement vaccination. Perceived behavioral control (i.e., money and time) was positively associated with intentions to implement C&D, vaccination, and stamping-out without any compensation. Results suggest that farmers are in favor of implementing preventive measures (i.e., C&D and vaccination) on HPAI control over facing the consequences of control measures (i.e., stamping-out); and HPAI control programs should primarily focus on incentivizing farmers complemented by programs aiming to improve farmers’ attitude. Thus, policy should be emphasized to preventive measures rather than control measures. Financial incentive-based instruments (e.g., price and performance bonus) can be used to increase the intention of farmers to implement C&D and vaccination. Trained injectors might help to save the time needed to vaccinate the entire flock can increase the intention of farmers to vaccinate their chickens. Also, informational instruments (e.g., education and communication) can be used to change and to improve the attitude of farmers to implement both measures.